ПРОФЕССОР Б.Н. СТРАДОМСКИЙ И ЕГО РОЛЬ В ОРГАНИЗАЦИИ БОРЬБЫ С МАЛЯРИЕЙ НА ЮГЕ РОССИИ - В. П. Терентьев; Н. И. Мамедова; Ю. М. Амбалов; М. З. Гасанов (SINAPS LLC, 2014)
The аrticle is devoted to the first head of the chair of infectious diseases of RGMI professor B.N. Stradomsky. In addition autobiographical data chronologically describes the way of becoming a great scientist and educator from a student, intern, the clinician to, head of chair of infectious diseases of Rostov state medical institute. Basic research B.N. Stradomsky were devoted to the diagnosis and treatment of malaria. Accumulated vast practical experience in malaria foci formed the basis of the thesis and monograph «To the question of the treatment of malaria». The article also shows the relevance of the conclusions B.N. Stradomsky malaria and at the present stage.